(untitled) (Academia Journal of Medicine, 2020)
Background: Sepsis is a systemic, deleterious host response to infection. Severe sepsis is defined as acute organ dysfunction secondary to documented or suspected infection and septic shock is severe sepsis with hypotension not reversed by fluid resuscitation. The present study was conducted to assess the determinants and outcomes of sepsis treated in medical wards and ICU. Subjects and Methods: The study was done at Subbaiah Institute of Medical Sciences, Shivamogga, Karnataka. 320 patients with sepsis of both genders were divided into 2 groups. Group I patients were admitted to the medical ward and group II to ICU. Clinical examination and laboratory tests were done. Results: Source of infection was a urinary tract in 12% in group I and 11% in group II, a respiratory tract in 40% in group IU and 32% in group II, GIT in 25% and 22% in group I and II respectively, blood infection in 15% and 20% in group I and II respectively and soft tissue infection in 8% and 15% in group I and II respectively. The difference was significant (P< 0.05). Appropriate specimen culture was present in 75 in group I and 64 in group II and blood culture in 42 in group I and 23 in group II. The difference was non-significant (P> 0.05). Conclusion: Clinical features and co-morbidities were higher in ICU patients as compared to the medical ward.